VD_FINDINFO Décision / 2011 / 355 vom 18. Januar 2011 - VD Tribunal cantonal (2011)
ABUS D'AUTORITÉ, CONSTATATION DES FAITS, PARTIE CIVILE | 312 CP, 126 CPP (CH), 398 al. 3 let. a CPP (CH), 398 al. 3 let. b CPP (CH)